Adsorption Kinetics for the Removal of Nitrite Ions from Aqueous Solutions by an Ion-Exchange Resin - Mehmet Kobya; Erhan Demirbaş; Serkan Yeşilot; Ruhtan Başkaya (Adsorption Science & Technology)
The adsorption kinetics of nitrite ions in aqueous solutions onto an anion-exchange resin A-250 was explored in a well-stirred tank. The capacity of the ion-exchange resin for the removal of nitrite ions from aqueous solution was investigated under different conditions, viz. initial concentration (10–50 mg/l), pH (2–8), particle size (565–850 μm) and resin dosage (2–8 g/l). A number of kinetic models such as those of external and intraparticle diffusion were applied to the results from this study in order to identify the adsorption mechanism. The results correlated well with the intraparticle diffusion model. The experimental parameters had an effect on the effective pore and surface diffusivities. Adsorption of nitrite ions onto the resin showed that the latter could be used as an efficient adsorbent material for the removal of nitrite ions from aqueous solutions.